(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Marketing has been interested in delving into the mechanisms through which promotional efforts encourage customers to purchase a specific item. in this study we discuss about The Role of Attitude in integrative models, Measuring Self-Image and Brand Personality in the Same Associative Network , Attitude formation and change, Dimensional attitude model, An integrated model of attitude and choice, Levels of interaction, The Relationship between attitude toward the ad and attitude toward the brand , Attitude towards firms’ brand likeability and purchase intention, Brand Extension Strategy, The influence of brand awareness on brand image, The influence of brand awareness on brand trust, Brand commitment